Reflections on African Americans in Baseball: No Longer the Vanguard of Change - Ruck, Rob (Race and social problems, 2021)
During the last decade, a number of athletes began engaging in social activism. In the aftermath of George Floyd’s death, that wave of protest became a tsunami, energizing collegiate and professional athletes and reverberating across society. But baseball, once in the vanguard of sports activism, remained on the sidelines. As the national pastime, it reflected the country’s turn toward social Darwinism and segregation at the turn of the 20th century. After World War II, when Jackie Robinson reintegrated the major leagues, it was a catalyst to change off the field. This essay addresses that politicized past and its more quiescent present.